Desire for the desert: racialising white teachers' motives for working in remote schools in the Australian desert. Issue 2 (4th March 2017) - Schulz, Samantha
Abstract: Distinct from rurality, the Australian desert has long functioned as a signifier of remoteness in the dominant imagination; a product of spatialised binary relations between 'progressive' (white) mainstream or idealised white countryside, and disordered/dangerous Aboriginal periphery. Remoteness constitutes a complex racial dynamic that has historically mediated white teachers' and missionaries' desires to travel to the social margins . This article adopts a discursive understanding of remoteness to examine contemporary white teachers' decisions to work in Aboriginal schools in the desert – decisions that are often articulated through unwitting recourse to the 'three Ms' or 'tourist'. The article explores these identity constructs and how they enable different performances of whiteness. It examines how white people's desires are often covertly raced but does not however, position the teacher as a priori racist. Rather, desire is theorised as a social construct in which subjects invest, which may at times contribute toward processes of decolonisation. This rendering moves beyond a logic of individualism and underpins the argument that recognising how these dynamics play out is vital with respect to understanding the place of white teachers inside remote Indigenous Education. Moreover, such insights are valuable for appreciating how whiteness continues to be reproduced in White Australia under a guise of good intentions.